A culturally-congruent sexuality education content for adolescent in Legazpi City - Mirandilla, Ma. Elma Lim
This study generated age-appropriate, culturally-congruent sexuality education content for adolescents 10-18 years old. It identified topics for each key concept designed for age categories: 10-12, 13-15 and 16-18 years old. The proposed sexuality education content was based on the consensus among teachers through three rounds of Delphi Technique using UNESCO’s International Technical Guidance on Sexuality Education. The consensus on key ideas and topics was supported by significant perceptions of local experts gathered through one-on-one interviews. The research was conducted in Legazpi City. All six key concepts and topics of the Technical Guidance were found acceptable across all age categories except for several key ideas. The key concepts include: Relationships; Values, Attitudes and Skills; Culture, Society and Human Rights; Human Development; Sexual Behavior; and Sexual and Reproductive Health. Probable reasons for excluding some key ideas under various key concepts may be ascribed to the attitudes of adults specifically, prohibitive silence and adultism. Teachers and key informants in this study believed that children were too young to understand and that providing them information will provoke curiosity and entice them to engage in sexual activity. Pursuing a culturally-sound and age-appropriate sexuality education content is indispensable at this time of globalization when adolescents are drawn close to reproductive health risks primarily due to their lack of information on their sexuality. Thus, an appropriate and comprehensive sexuality education program is a significant preventive strategy.